CURRENT TRENDS IN E-LEARNING DEVELOPMENT - MARESOVA, Hana; KLEMENT, Milan (Journal of Technology and Information Education, 2012)
The article focuses on the analysis the new possibilities of e-learning development, which is currently reaching its limits in both of e-learning applications and the e-learning distance study supports created in text forms with using multimedia. There are analyzed the possible outlines of development towards to the use of multiuser virtual environment in e-learning education.
Keywords: e-learning; multiuser virtual environment; information and communication